2015
DOI: 10.1002/pmic.201500157
|View full text |Cite
|
Sign up to set email alerts
|

Saliva proteome profiling reveals potential salivary biomarkers for detection of oral cavity squamous cell carcinoma

Abstract: Oral cavity squamous cell carcinoma (OSCC), which is frequently associated with poor prognosis and mortality, is a leading cause of cancer-related death worldwide. Discovery of body fluid accessible biomarkers is needed to improve OSCC screening. To this end, we profiled proteomes of saliva from the healthy volunteers, the individuals with oral potentially malignant disorders (OPMD), and the OSCC patients by means of SDS-PAGE coupled with LC-MS/MS. In the control, the OPMD, and the OSCC groups, 958, 845, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…Among these, resistin (RETN) was validated by ELISA thus confirming proteomic data. RETN levels had significant correlation with late-stage primary tumours, advanced overall stage and lymphnode metastasis 20 . The same group used a spectral counting-based label free quantification platform to identify 64 protein candidates for OSCC 21 .…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…Among these, resistin (RETN) was validated by ELISA thus confirming proteomic data. RETN levels had significant correlation with late-stage primary tumours, advanced overall stage and lymphnode metastasis 20 . The same group used a spectral counting-based label free quantification platform to identify 64 protein candidates for OSCC 21 .…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…investigated the saliva proteome for biomarkers discovery of oral cavity squamous cell carcinoma, and identified 1173 protein in three samples, among which 742 proteins were quantified with label‐free strategy . Among these studies, quite a number of salivary proteins were found to be associated with cancers and other diseases such as Sjögren's syndrome , type‐2 diabetes , and different oral pathologies . However, the proteomic analysis of saliva in oral ulcer, one of the most common oral diseases, is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…PPE is defined as any exudative effusion associated with pneumonia, lung abscess, or bronchiectasis and is further classified as UPPE or CPPE. CPPE is defined as the presence of PPE with one of the following additional criteria: (1) pH < 7.2; (2) glucose < 60 mg/dl; (3) LDH > 1000 U/l; (4) bacteria found on Gram’s stain or culture; or (5) frank pus 3, 12 . Patients received pleural drainage or surgery for the treatment of their PPEs based on previously accepted guidelines [3].…”
Section: Methodsmentioning
confidence: 99%